2011
DOI: 10.4314/ijest.v2i7.63733
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cadmium (II) from aqueous solutions by two kinds of manganese coagulants

Abstract: The study presents the removal of trace cadmium (II) in water with batch experiments by two kinds of manganese coagulants, HMO prepared from KMnO 4 and Na 2 S 2 O 3 , and HFMO prepared from KMnO 4 and FeSO 4 . Various parameters such as turbidity, pH, initial concentration of Cd(II) and coagulation time were investigated. The results showed that the cadmium can be better removed using HMO than by HFMO. With pH =6.72 and the Cd(II) initial concentration, 1mg/L, the dosage of HMO is 20mg/L, as the removal rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…The concentration of Cd was reduced to low levels by both the precipitants. Xu [33] carried out batch studies with two types of manganese coagulants, HMO prepared from KMnO 4 and Na 2 S 2 O 3 and HMFO prepared from KMnO 4 and Fe 2 SO 4 . Results revealed that HMO is an efficient coagulant for removal of trace Cd from water.…”
Section: Coagulation/flocculationmentioning
confidence: 99%
“…The concentration of Cd was reduced to low levels by both the precipitants. Xu [33] carried out batch studies with two types of manganese coagulants, HMO prepared from KMnO 4 and Na 2 S 2 O 3 and HMFO prepared from KMnO 4 and Fe 2 SO 4 . Results revealed that HMO is an efficient coagulant for removal of trace Cd from water.…”
Section: Coagulation/flocculationmentioning
confidence: 99%
“…Although many different methods such as chemical precipitation [7,16], ion exchange [17], solvent extraction [18,19], reverse osmosis [20], dialysis/electrodialysis [21], supported liquid membrane [22] and adsorption [23][24][25] have been documented for the removal of heavy metal ions, the process based on adsorption methods is promising, due to its low cost and high removal efficiency [26]. Many low-cost materials [27][28][29][30][31][32][33][34][35][36] have been reported for Cd(II) removal from water and wastewater systems, but they are not very popular because of various limitation like cost, removal efficiency and maintenance.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Large IL to water ratio quantity (1:1) was also employed (Earle and Seddon, 2000;Sereshti et al, 2014). Moreover, the extraction activities using ionic liquids were carried out from water samples containing far greater concentrations (Hernandez et al, 2010) than the metal ions found in real samples (Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%